Bukittinggi City Space Transformation Based on Tourism Development - Rinaldi Mirsa; Muhammad; Fidyati; Gustika Rahayu (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2022)
Bukittinggi City is a city in West Sumatra Province that is one of the popular tourist destinations for the public and tourists. The existence of tourist objects around the city center greatly affects the structure of urban space, in the use of space itself, it is very visible from the distribution of tourist facilities locations that spread around tourist objects that can attract hospitality and trade activities that spread to the downtown area in Bukittinggi. This study aims to determine how the spatial transformation of Bukittinggi City is based on tourism development from 1984 to 2021 and the factors that influence the development of the space. The method used in this research is qualitative. This study found that the City of Bukittinggi when viewed from the area of ​​development of the City of Bukittinggi reflects a concentric pattern, this can be seen from the location of the city of Ngarai Sianok which limits the development of the city to the west and north. Based on the performance agreement letter from the Public Works and Spatial Planning Office of Bukittinggi City in 2020, the percentage of suitability for spatial planning and utilization is 37.50%. The building mass in a developing tourist attraction has a heterogeneous textured area texture, where the shape of the mass and space configuration have different sizes, shapes, and densities. The high density of building mass only occurs in the core area of ​​the city with a percentage above 80%. The Bukittinggi City Regional Spatial Plan article 28 paragraph 2 explains that there are 5 types of road networks, namely primary arterial roads, secondary arteries, secondary collectors, local roads, and freeways. The road network in Bukittinggi City is growing rapidly towards the city center and in several residential areas. The distribution of tourist facilities is generally located in the city center and a small part is spread along Jalan Soekarno Hatta and Jalan Sudirman. The distribution of tourist objects has formed a concentric space in the city's core area with local and regional service scales.